Musculoskeletal deterioration in men accompanies increases in body fat. (2nd December 2013) - Pasco, Julie A; Gould, Haslinda; Brennan, Sharon L; Nicholson, Geoff C.; Kotowicz, Mark A
<x xml:space="preserve">Abstract</x> Objective To examine body fat and musculoskeletal changes in men over 5 years. Methods Body composition was evaluated for men in the Geelong Osteoporosis Study using whole body dual energy X‐ray absorptiometry (DXA) during two time‐periods. DXA was performed for 1329 men (25‐96 years) during 2001‐2006 and for 900 men (25‐98 years), 2006‐2011. The masses of fat, lean, and bone were expressed relative to the square of height (kg/m2). Each compartment was also expressed as a percentage relative to body weight (%fat, %lean, %bone). Results Mean BMI increased from 26.9 kg/m2 in 2001‐2006, to 27.2 kg/m2 in 2006‐2011 (P = 0.04). Mean fat mass increased by 9.0% from 6.98 kg/m2 (95%CI 6.84‐7.11) in 2001‐2006, to 7.60 kg/m2 (7.44‐7.77) in 2006‐2011 (P < 0.001); mean lean mass decreased by 0.9%, from 18.92 kg/m2 (18.83‐19.01) to 18.75 kg/m2 (18.64‐18.86) (P = 0.02), and mean bone mass decreased 1.6% from 1.041 kg/m2 (1.034‐1.047), to 1.024 kg/m2 (1.016‐1.032). Mean %fat increased from 23.4% to 25.2%, mean %lean decreased from 72.6% to 70.9% and mean %bone decreased from 4.0% to 3.9% (all P < 0.05). Conclusions An increase in BMI, which reflects a substantial increase in body fat mass and declines in both lean and bone mass was reported. This may have implications for future development of bone fragility, sarcopenia, and sarcopenic obesity.